Systematic analysis of long non-coding RNA and mRNA expression changes in ApoE-deficient mice during atherosclerosis - Xiaoqian Lou; Xiaoyan Ma; Dawei Wang; Xiangjun Li; Bo Sun; Tong Zhang; Meng Qin; Liqun Ren (Molecular and Cellular Biochemistry, 2019)
Atherosclerosis plays an important role in the pathology of coronary heart disease, cerebrovascular disease, and systemic vascular disease. Long non-coding RNAs (lncRNAs) are involved in most biological processes and are deregulated in many human diseases. However, the expression alteration and precise role of lncRNAs during atherosclerosis are unknown. We report here the systematic profiling of lncRNAs and mRNAs in an ApoE-deficient (ApoE − / − ) mouse model of atherosclerosis. Clariom D solutions for the mouse Affymetrix Gene Chip were employed to analyze the RNAs from control and ApoE − / − mice. The functions of the differentially expressed mRNAs and lncRNAs and the relationships of their expression with atherosclerosis were analyzed by gene ontology, co-expression network, pathway enrichment, and lncRNA target pathway network analyses. Quantitative real-time PCR (QRT-PCR) was used to determine the expression of mRNAs and lncRNAs. A total of 2212 differentially expressed lncRNAs were identified in ApoE − / − mice, including 1186 up-regulated and 1026 down-regulated lncRNAs (|FC| ≥ 1.1, p < 0.05). A total of 1190 differentially expressed mRNAs were found in the ApoE − / − mice with 384 up-regulated and 806 down-regulated (|FC| ≥ 1.1, p < 0.05). Bioinformatics analyses demonstrated extensive co-expression of lncRNAs and mRNAs and concomitant deregulation of multiple signaling pathways associated with the initiation and progression of atherosclerosis. The identified differentially expressed mRNAs and lncRNAs as well as the related signaling pathways may provide systematic information for understanding the pathogenesis and identifying biomarkers for the diagnosis, treatment, and prognosis of atherosclerosis.